EFEKTIVITAS BIMBINGAN KELOMPOK (TEKNIK ROLE PLAYING) DALAM MENINGKATKAN SELF-ESTEEM PADA SISWA KELAS VIII DI SMP NEGERI 12 PALU - Iffah Nur Fathiyah; Ridwan Syahran; Mardi Lestari; Micha Felayati Silalahi (ACADEMIA: Jurnal Inovasi Riset Akademik, 2026)
Low self-esteem among adolescents has a direct impact on self-confidence, the quality of social interactions, and students’ learning motivation. This condition was identified among eighth-grade students at SMP Negeri 12 Palu, as indicated by tendencies to feel inferior, frequently compare themselves to others, avoid social interactions, and easily give up when facing difficulties. This study aimed to examine the effectiveness of group guidance services using the role-playing technique in improving the self-esteem of eighth-grade students at SMP Negeri 12 Palu. This research employed a quantitative approach with a pre-experimental method using a one-group pretest-posttest design. The research participants consisted of eighth-grade students who were identified as having low levels of self-esteem. Data were collected through a closed-ended Likert-scale questionnaire administered before and after the intervention, while data analysis was conducted using descriptive statistics and the Wilcoxon Signed Rank Test. The findings revealed that prior to the intervention, all participants were categorized as having low or very low self-esteem. After participating in the group guidance sessions, all students demonstrated significant improvement, reaching high and very high self-esteem categories. The Wilcoxon test confirmed that the improvement was statistically significant, leading to the rejection of the null hypothesis and indicating that group guidance services utilizing the role-playing technique were effective. Based on these findings, school counselors are encouraged to implement this service as a routine preventive program. Future research is expected to broaden the scope of participants and incorporate additional relevant variables to further investigate factors associated with students’ self-esteem. ABSTRAK Rendahnya self-esteem pada remaja memberikan dampak langsung terhadap kepercayaan diri, kualitas interaksi sosial, serta motivasi belajar siswa. Kondisi ini teridentifikasi pada siswa kelas VIII di SMP Negeri 12 Palu, yang ditandai dengan kecenderungan mudah minder, sering membandingkan diri dengan orang lain, menghindari pergaulan, serta mudah menyerah ketika menghadapi kesulitan. Penelitian ini bertujuan untuk menguji tingkat efektivitas layanan bimbingan kelompok dengan teknik role playing dalam meningkatkan self-esteem siswa kelas VIII di SMP Negeri 12 Palu. Pendekatan yang digunakan dalam penelitian ini adalah kuantitatif, dengan metode pre-eksperimen melalui desain one group pretest-posttest. Subjek penelitian terdiri atas siswa kelas VIII yang teridentifikasi memiliki tingkat self-esteem rendah. Pengumpulan data dilakukan melalui angket tertutup berskala Likert yang diberikan baik sebelum maupun sesudah pemberian layanan, sementara analisis data dilakukan menggunakan statistik deskriptif serta uji Wilcoxon Signed Rank Test. Hasil penelitian menunjukkan bahwa sebelum perlakuan diberikan, seluruh siswa berada pada kategori self-esteem rendah dan sangat rendah, sedangkan setelah mengikuti layanan, seluruh siswa mengalami peningkatan yang signifikan menuju kategori tinggi dan sangat tinggi. Uji Wilcoxon membuktikan bahwa peningkatan tersebut bermakna secara statistik, sehingga hipotesis nol dinyatakan ditolak dan layanan bimbingan kelompok dengan teknik role playing terbukti efektif. Berdasarkan temuan tersebut, guru BK disarankan untuk menjadikan layanan ini sebagai program preventif yang dilaksanakan secara rutin, sementara penelitian selanjutnya diharapkan dapat memperluas cakupan subjek penelitian serta menambahkan variabel-variabel relevan lainnya.